Flies in the Qur'an Perspective of Tafsir Ilmi - M. Fajar (PT. Pustaka Cendekia Publisher, 2025)
The Qur'an is a miracle of the Prophet Muhammad whose authenticity has been maintained to this day. The more advanced science becomes, the more visible the validity of its miracles. Many non-Muslim scientists are reluctant to convert to Islam after researching the Koran more deeply. The Koran also contains a lot of science and knowledge if humans can see it from various aspects. In this case, the author will discuss flies, which are one of the animals with perfect metamorphosis. In metamorphosis, several changes and phases occur after the fly hatches its eggs. This research method is research that uses qualitative research using literature study. The type of data collected is primary data, namely tafsir books and secondary data, namely books, articles, journals and literature related to the Koran and flies. Researchers want to know the secret and wisdom of choosing flies as a parable in these letters and verses.